Influence of the hydrogen saturation temperature on the structure of melt-spun Ti₃₀Zr₄₅Ni₂₅ alloy - Dmytrenko, O.Ye.; Kolodiy, I.V. (Вопросы атомной науки и техники, 2018)
The influence of hydrogen saturation temperature on the structure and phase composition of the melt-spun Ti₃₀Zr₄₅Ni₂₅ alloys, heat-treated in hydrogen atmosphere at different temperatures (400, 450, 500 °C) for 4 hours, was studied. Using X-ray diffraction analysis it was found that hydrides, formed during the hydrogenation process, were based on the Laves phase L-TiZrNi and (Ti, Zr)₂Ni, α-(Ti, Zr) phases. Structural models of these phases were constructed and a model for filling these phases with hydrogen was presented. Electron microscopic study showed that the surface of the samples had no significant changes during the hydrogenation process. Also, it was established the influence of the hydrogenation temperature on the concentration of oxygen and nitrogen gas impurities in the samples. Проведено дослідження впливу температури насичення воднем на структурно-фазовий склад зразків швидкозагартованого сплаву Ti₃₀Zr₄₅Ni₂₅ після термообробки в атмосфері водню при різних температурах (400, 450, 500 °С) протягом 4 год. Методом рентгеноструктурного аналізу встановлено, що в процесі насичення воднем утворюються гідриди на основі фази Лавеса L-TiZrNi (С14), фази (Ti,Zr)₂Ni та α-(Ti, Zr). Побудовано структурні моделі фаз, присутніх у досліджуваних зразках, і представлена модель заповнення цих фаз воднем. Проведено електронно-мікроскопічне дослідження поверхні зразків і показано, що поверхня зразків не зазнає істотних змін у процесі насичення воднем. Встановлено вплив температури насичення воднем на концентрацію газових домішок кисню та азоту. Проведено исследование влияния температуры насыщения водородом на структурно-фазовый состав образцов быстрозакаленного сплава Ti₃₀Zr₄₅Ni₂₅, подвергнутых термообработке в атмосфере водорода, при различных температурах (400, 450, 500 °С) в течение 4 ч. Методом рентгеноструктурного анализа установлено, что в процессе наводорoживания образуются гидриды на основе фазы Лавеса L-TiZrNi (С14), фазы (Ti, Zr)₂Ni и α-(Ti, Zr). Построены структурные модели фаз, присутствующих в исследуемых образцах, и представлена модель заполнения этих фаз водородом. Проведено электронно-микроскопическое исследование поверхности образцов и показано, что поверхность образцов не претерпевает существенных изменений в процессе насыщения водородом. Установлено влияние температуры наводорoживания на концентрацию газовых примесей кислорода и азота.